Feeding Habits of Leopards and Leopard Cats in the Fragmented Forests Surrounding the Kathmandu Valley - Prajwol Manandhar; Keren S. Pereira; Naresh Kusi; Jyoti Joshi; Noam Levin; Hemanta K. Chaudhary; Claudia Wultsch; Sandesh Lamichhane; Suman Bhandari; Laba Guragain; Rajesh M. Rajbhandari; Berndt J. V. Rensburg; et al. (Ecology and Evolution)
ABSTRACT Large‐scale anthropogenic developments in the metropolitan areas of Nepal and the rural to urban influx of people have exacerbated human–wildlife conflicts across human‐altered landscapes of Nepal. The Kathmandu Valley has experienced large‐scale urbanization and has subsequently witnessed substantial incidents of human–wildlife conflicts given the increasing levels of human encroachment into remnant wildlife habitats. Here, we applied DNA metabarcoding in combination with geospatial analysis to study the feeding ecology of two urban carnivores, the leopard (Panthera pardus) and the leopard cat (Prionailurus bengalensis), in the forests surrounding the Kathmandu Valley and to check whether the leopards' predation on domestic animals contributes to human‐leopard conflict in this region and to obtain a baseline data on the dietary habits of the poorly studied leopard cat. We found that leopards were highly dependent on domestic animals in areas dominated by human‐use activities (agricultural and built‐up areas), whereas leopard cats mostly predated on wild rodents. Through our work, we highlight the importance of domestic prey in the diets of urban carnivores like leopards and demonstrate the influence human‐induced habitat disturbance has on the ecology of local wildlife. This study generates critical information which will help to inform conflict mitigation strategies and conservation planning for the two carnivore species, in addition to identifying areas within the region that are susceptible to human–wildlife conflicts.